Analysis of the impact on the stock market of chemical disasters: petrochemical companies in industrial complex in Korea - Eun, Sungtae, author; Loomis, John B., advisor; Kroll, Stephan, committee member; Iverson, Terrence, committee member (Colorado State University. Libraries, 2014)
The chemical industries in Korea have the industrial structure of a developing country focused more on basic chemical compounds and wider use of products rather than fine chemical goods. The chemical industry is composed of 10% knowledge (pharmaceuticals), 30% specialty (consumer products, agricultural chemicals, coatings, and fine chemicals), and 60% basic (polymers, synthetic rubber and fibers, basic inorganic chemicals, and basic organic chemicals). This study examined 18 different petrochemical, food chemical and steel companies with 26 chemical disasters. Capelle-Blancard, Laguna (2010) showed the problems related to providing robust empirical evidences on the stock market reaction to chemical disasters. This analysis which was based on using abnormal returns (ARs) and cumulative abnormal returns (CARs) concluded that chemical disasters like explosions, plant fires, and chemical leaks caused both negative and positive stock market reaction. Most of the companies that I tried to test the hypotheses showed negative ARs and CARs after the event as I expected. I thought that the effects on stock market reactions were different according to the type, extent, and number of casualties in the accident. When I performed the event study with the topic, I got the results from 15 cases of the relationships between the ARs or CARs and the extent, type, and the number of casualties. However, all of the cases did not show the same results. The 16 cases revealed that the degree of severity of the chemical accidents was not really related to the market reaction. The reason why the unmatched results arose was because of the exposure of the event information. Hamilton (1995) mentioned that the market is influenced by the leak of information. I have concluded that the relationship between the ARs/CARs and the extent, type, and the number of casualties are not seriously related to each other. There is a limitation to this conclusion because of the leak of information to the market (Hamilton, 1995). Korajczyk, Lucas, and McDonald (1990) mentioned the asymmetry should be of greatest concern to potential buyers of common stock. That means there should be a factor(s) affect(s) the market and its behavior. The country like Korea is likely to conceal or control the information of the chemical disasters. According to the Center for Occupational Environmental Health (COEH) in Korea, there was a briefing session in June 2013 about the current state of concealment of fires, explosions and chemical spills in industrial complexes at the congress. The statistical data investigation in the accident has a couple of problems. First, there is no report of the accident to local authority if the petrochemical plant doesn't have death casualties. Second, there are differences in the accident statistics between the central and the local government. Lastly, the classification of industrial accidents is not established precisely.
Keywords: chemical accidents; stock market in Korea; environmental disasters